2016
DOI: 10.1088/0964-1726/25/2/025009
|View full text |Cite
|
Sign up to set email alerts
|

Unimode metamaterials exhibiting negative linear compressibility and negative thermal expansion

Abstract: Unimode metamaterials made from rotating rigid triangles are analysed mathematically for their mechanical and thermal expansion properties. It is shown that these unimode systems exhibit positive Poisson's ratios irrespective of size, shape and angle of aperture, with the Poisson's ratio exhibiting giant values for certain conformations. When the Poisson's ratio in one loading direction is larger than +1, the systems were found to exhibit the anomalous property of negative linear compressibility along this dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 64 publications
3
57
0
1
Order By: Relevance
“…And the expressions of Poisson's ratios of these two models are same due to the same framework structure so the euqation, β L (OX i ) (Model I) = 2 β L (OX i ) (Model III) , can be easily to understand. More than that, through the comparison of these two models, it can be indicated that in addition to the geometry features which have already been widely discussed , the arrangement of the framework structure can also have a great effect on the compressibility properties and arranging the framework in a dense way just like the Model III is not conductive to the enhancement of negative compressibility effect.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…And the expressions of Poisson's ratios of these two models are same due to the same framework structure so the euqation, β L (OX i ) (Model I) = 2 β L (OX i ) (Model III) , can be easily to understand. More than that, through the comparison of these two models, it can be indicated that in addition to the geometry features which have already been widely discussed , the arrangement of the framework structure can also have a great effect on the compressibility properties and arranging the framework in a dense way just like the Model III is not conductive to the enhancement of negative compressibility effect.…”
Section: Discussionmentioning
confidence: 95%
“…By using a combination of finite element simulations and analytical derivations, it was shown that NLC can be exhibited in body‐ or face‐centered tetragonal structures . It has also been shown that some systems made from rotating rigid units which are usually associated with auxeticity can also exhibit negative linear compressibility for certain conditions . Moreover Miller et al identified several relatively common materials which displayed NLC and presented several potential applications.…”
Section: Introductionmentioning
confidence: 99%
“…Here it should be mentioned that, apart from the planar rotational structures (for example, rotating rigid squares, parallelograms, triangles, etc. [26][27][28][29][30][31][32]), 3D rotational structures constructed of cubes linked at certain edges or vertices, either directly or through ligaments [71][72][73], can also be employed. When such systems are stretched or compressed, the cubic units rotate and angles between the adjacent sides change, leading to spatial expansion or shrinkage that may be conducive of auxetic behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Note that the factor of 2 is necessary, since it is being assumed that triangular units are located both above and below the plane of the 'rotating squares', where they could either have the same base-in which case the aforementioned triangular unit would be half of a rhombic structure, having diagonals of length r and 2h (see Figure 1)-or at different locations. The use of rhombic units, having triangular units both above and below the 'rotating squares base' and forming a wine-rack/Milton's unimode-like system [31,43,44], has the advantage that the system is easily tessellatable and will not shear. Note also that, assuming that the squares are perfectly rigid (as is normally assumed in the idealized 'rotating squares' model), the length r is a function of the single variable θ, the angles between the squares, and is given by:…”
Section: Referring Tomentioning
confidence: 99%
See 1 more Smart Citation